Charcoal production from Acromonia aculeata (Macaúba) and its impact on the environment - Barbosa, Sandro L.; de S. Freitas, Milton; de Souza Freitas, Natália; Nelson, David L.; Klein, Stanlei I. [UNESP] (My University, 2023)
Macaúba (Acrocomia aculeata) vegetable oil is concentrated in the fruit mesocarp and kernels, equivalent to about 55.7% and 45.8% of the mass the fruit respectively. The estimated world production of the fruit in 2017 was 266 million tons, based on the amount of Macaúba oil produced and the average content of oils in the fruit mesocarp and kernel. The processing of Macaúba for the extraction of vegetable oil for the synthesis of biodiesel involves the generation of a considerable volume of residue, and the pulp is equivalent to about 50% of the fruit mass. In addition, after the extraction of the oil, the pulp cake constitutes one of the main residues generated in the processing of Macaúba fruits. Activated charcoal was synthesized from the endocarp of the fruit of Acrocomia aculeata (Macaúba) by chemical activation using zinc chloride as an activating agent, resulting in a mesoporous material with a surface area of 627 m2 g-1 and a pore volume of 0.39 m3 g-1. The activated charcoal obtained contained Bronsted acid sites of 118.23 pmolg 1 and Lewis acid sites of 104.86 pmolg-1. Charcoal was successfully applied as an adsorptive agent in the purification of glycerol through the retention of fatty material.
Keywords: Activated charcoal; Byproduct; Friendly environmental process; Green chemistry; Macaúba